Zakat Profesi Dalam Pandangan Hukum Islam - Bachrul Ulum (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2020)
Poverty is one of the problems that often occurs in a country, this problem has become the world's attention because the whole world certainly experiences the problem of poverty affecting its citizens even though the impact is different from one country to another, especially Indonesia certainly experiences the problem of poverty among its citizens. , With this, one Islamic teaching is actually sufficient to be a solution to the differences, namely the concept of zakat being an obligation, where rich people are the main actors and poor people are the main target so that zakat can be carried out. Before discussing zakat, let's first understand what actually is zakat? , and what is the real purpose of enforcing zakat? Zakat linguistically has the meaning of increasing or developing, while zakat according to the term is the name for a special property, owned by certain people and given to certain people. According to Dr. Nuruddin Al Khodimy in his book al-Ijtihadul Maqosidy states that one of the most important goals of zakat is to increase love between the needy and the poor so that there is no distinction between the two so that they can unite in the bonds of brotherhood in Islam. Poverty that occurs, especially in Indonesia, can actually be overcome when zakat is truly implemented and truly carried out.